2020
DOI: 10.1007/s10948-019-05378-0
|View full text |Cite
|
Sign up to set email alerts
|

Strain Induced Orbital Dynamics Across the Metal Insulator Transition in Thin VO2/TiO2 (001) Films

Abstract: VO2 is a strongly correlated material, which undergoes a reversible metal insulator transition (MIT) coupled to a structural phase transition upon heating (T= 67° C). Since its discovery the nature of the insulating state has long been debated and different solid-state mechanisms have been proposed to explain its nature: Mott-Hubbard correlation, Peierls distortion or a combination of both. Moreover, still now there is a lack of consensus on the interplay between the different degrees of freedom: charge, latti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…This means the spectral weight transfer is a direct result of lattice and correlation interplay that is strongly enhanced in the [110] growth, because neither alone can reproduce experiment. We additionally see similar effects in the [100] growth orientation where explicit lattice symmetry breaking does not occur, but spectral signatures of correlation enhancement persist [43,44]. Ultimately, the evolution of the XAS waveform represents an experimental signature that non-local correlations have broken the equivalence between the two vanadium sites in the rutile phase, and the spectral features are quantitatively reproduced by a first principles analysis.…”
Section: Introduction -mentioning
confidence: 57%
See 1 more Smart Citation
“…This means the spectral weight transfer is a direct result of lattice and correlation interplay that is strongly enhanced in the [110] growth, because neither alone can reproduce experiment. We additionally see similar effects in the [100] growth orientation where explicit lattice symmetry breaking does not occur, but spectral signatures of correlation enhancement persist [43,44]. Ultimately, the evolution of the XAS waveform represents an experimental signature that non-local correlations have broken the equivalence between the two vanadium sites in the rutile phase, and the spectral features are quantitatively reproduced by a first principles analysis.…”
Section: Introduction -mentioning
confidence: 57%
“…While the resistivity switching in these new memristors is acheived by driving in a non-equilibrium thermal enviornment, disputes remain as to the origin of the switching [37]. This situation has redirected massive experimental efforts towards understanding epitaxial VO 2 thin films using TiO 2 substrates, which offer the possibility of enhancing electron correlation effects with severe strain even before the Peierls distortion [38][39][40][41][42][43][44].…”
Section: Introduction -mentioning
confidence: 99%
“…Advances on quantum mechanics of orbital physics which is today a hot topic have been obtained by Oleś group showing orbital dilution in d 4 oxides by tuning crystal field potential [96] and magnetic properties of crystalline and ferroelectric layered rare-earth-titanate by Kuznetsov et al [97]. Strain Induced orbital dynamics across the metal insulator transition in thin VO 2 films [98] provide further information on nanoscale phase separation in the correlation-driven insulator-metal transition in vanadium dioxide [99][100][101][102]. The theoretical studies on nanoscale phase separation observed in cuprates [103][104][105][106] have focused on the coexistence of a metallic phase with a spin density wave phase controlled by pressure [107] of the nucleation of magnetic micro-inhomogeneity induced by an electric field [108] the order-disorder transition in a system made of two electronic components induced by nearest-neighbor repulsion [109].…”
Section: The Superstripes 2019 Conferencementioning
confidence: 99%
“…Nowadays synchrotron radiation (SR) sources and X-ray freeelectron lasers (XFELs) provide powerful and brilliant X-ray beams that allow the structure and dynamics of matter to be investigated from atomic to mesoscale distances (Tsuji et al, 2004). Actually, brilliant X-ray spots are becoming more and more important for studying complex and functional materials at low dimensions or complex phenomena such as straindriven metal-insulator transition strongly correlated systems (D'Elia et al 2020), structural confinement in semiconducting nanowires (Rezvani et al, 2016;Pinto et al, 2016) and electrochemical dynamics of metal oxide nanoparticles (Rezvani et al, 2018;Pasqualini et al, 2017). Hence, generating a brilliant spot size is a challenging issue, but extremely important for a large class of experiments.…”
Section: Introductionmentioning
confidence: 99%